Variation in structure and composition of two pine forests in Kailash Sacred Landscape, Nepal - Subedi, C. K.; Gurung, J.; Ghimire, S. K.; Chettri, N.; Pasakhala, B.; Bhandari, P.; Chaudhary, R. P. (Banko Janakari, 2018)
Chir pine (Pinus roxburghii Sarg.) and blue pine (Pinus wallichiana A.B. Jacks.) are two common species found in mid-hill forests of Nepal where households largely depend on forest resources for their livelihoods and subsistence. The management of such forests is supported by our understanding of the dynamics in forest structure and species composition and the relationship between different forest community characteristics. This study was designed to determine the variation in species composition and the relationship between various forest community characteristics in two pine forests of Kailash Sacred Landscape, Nepal. Quadrat sampling was applied to collect information on forest species, forest community structure, and disturbance factors.Data was statistically analyzed using IBM SPSS. There were a total of 31 plant species under 28 genera and 20 families in the P. roxburghii forest, and 38 plant species under 37 genera and 19 families in the P. wallichiana forest. Mean DBH, height and canopy diameter of P. roxburghii was 23.98 cm, 12.77 m and 1.97 m, respectively, and that of P. wallichiana was 31.5 cm, 11.48 m and 2.79 m, respectively. The relationship between DBH and both height and crown diameter showed strong relationships in the two forest types. In both forests, DBH and height class distribution showed a hump-shaped (unimodal type) distribution with a greater proportion of medium-sized individuals that indicated disruptive forest regeneration. Fire and tree cut were significant disturbance factors in P. roxburghii forest, while grazing and trampling were significant in P. wallichiana forest. The extent of these disturbance factors as determinants of regeneration and species recruitment is important to assess for effective forest management. Banko Janakari A Journal of Forestry Information for Nepal Vol. 28, No. 1, 2018, page: 26-36